XRD In Situ Observation of Carbothermic Reduction of Magnetite Powder in Microwave Electric and Magnetic Fields. Issue 10 (2nd April 2013) - Sabelström, Nils; Hayashi, Miyuki; Yokoyama, Yuki; Watanabe, Takashi; Nagata, Kazuhiro
Abstract: Recently, microwave energy is expected to be a heat source for high temperature process aiming at CO2 reduction and energy conservation owing to the possibility of volumetric and selective heating. In order to examine the applicability of microwave heating to ironmaking, a basic research may be required with respect to the heating mechanism of raw and product materials of ironmaking as well as the carbothermic reduction mechanism of iron ore. To carry out this research, the authors have developed a single mode microwave furnace combined with X‐ray diffraction analysis. By using this, the authors have elucidated the effects of electric and magnetic fields of microwave on carbothermic reduction of magnetite powders, and have observed the selective heating of materials. It has been found that the Fe3 O4 –C mixed powders are more rapidly heated by the magnetic field than by the electric field just after the onset of heating. The rapid heating owing to the magnetic field is associated with the magnetic loss of Fe3 O4 powders. With respect to the magnetic field heating, once the temperature increases up to 800–1000°C, the temperature does not increase and the reduction hardly progresses, which may stem from the decrement in the microwave absorption of the sample. The main heat source is C at this stage. On the other hand, temperature monotonically increases up to around 1000°C and reaction gradually progresses for the electric field heating. It is considered that the main energy absorber is C at the beginning, and then is possibly changed to FeO at elevated temperatures. Abstract : Microwave energy is expected to be a heat source for high temperature process aiming at CO2 reduction and energy conservation owing to the possibility of volumetric and selective heating. In order to examine the applicability of microwave heating to ironmaking, a basic research was conducted with respect to the heating mechanism of raw and product materials of ironmaking as well as the carbothermic reduction mechanism of iron oxide using a single mode microwave furnace combined with X‐ray diffraction analysis.